The Church’s Forgotten “Third Lung” - P. Brock, Sebastian (Asian Horizons, 2025)
The article provides the context of the suggestion made earlier that the Church needs to breathe, not just with Pope John Paul II’s ‘two lungs’ (Latin West and Greek East), but with a forgotten ‘third lung’ as well, the Syriac Orient, representing the indigenous Churches of West Asia. Since the geopolitical upheavals in West Asia in the last decades have led to large-scale emigration, this has greatly weakened the homeland base of the ‘Syriac Orient’ in that region, and as a result, it is now the Syriac Churches of India which constitute the most stable locus in the world of the Syriac Orient. This carries with it the responsibility for ensuring the appropriate fostering and maintaining of that tradition - a responsibility it owes to all the Christian Churches, and not just to those belonging to the Syriac Orient.